2014
DOI: 10.1080/15332667.2014.882626
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships Between Businesses and NGOs in the Field of Corporate Social Responsibility: A Model of Success From the Perspective of Relationship Marketing

Abstract: Social alliances have become a mechanism that businesses and nongovernmental organizations (NGOs) have adopted in order to work together to address complex social problems that neither sector alone has the knowledge and resources needed to deal with appropriately. In combining the 2 different perspectives, these partnerships can create mutual value. Many such alliances have, however, been unsuccessful. The present work focuses on designing a theoretical model of successful partnerships between businesses and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 79 publications
3
13
0
3
Order By: Relevance
“…With the proliferation of SAVC, not-for-profit actors have become a facilitating hub as they connect their organizations to business actors for better, long-term, sustainable development activities (Thiele et al, 2011). They help the business actors in governance functions, capacity building, sustainable agricultural technology, gender groups, market information and trade activities (Barroso-Méndez et al, 2014).…”
Section: Not-for-profit Actor: From Cooperation To Collaborationmentioning
confidence: 99%
See 1 more Smart Citation
“…With the proliferation of SAVC, not-for-profit actors have become a facilitating hub as they connect their organizations to business actors for better, long-term, sustainable development activities (Thiele et al, 2011). They help the business actors in governance functions, capacity building, sustainable agricultural technology, gender groups, market information and trade activities (Barroso-Méndez et al, 2014).…”
Section: Not-for-profit Actor: From Cooperation To Collaborationmentioning
confidence: 99%
“…Lambert and Cooper (2000) have indicated that the supply chain constitutes all producers and service providers with whom the focal actor interacts directly or indirectly (Fearne, 1998). According to Barroso-Méndez et al (2014), it is neces- Firms occasionally adjust their scale and scope of operations. This may accommodate a change in relationship paradigm and information management (Thiele et al, 2011).…”
Section: Product Flow and Interactionmentioning
confidence: 99%
“…Consumers feel special when invited to events of a brand, they feel a part of the brands' world [43] 18. This chocolate brand has social responsibility programs/actions Consumers value brands that foster partnerships with social programs and actions, such as the support for NGOs [77] 22. This chocolate brand is known for its social responsibility…”
Section: Factor Item Description Theoretical Supportmentioning
confidence: 99%
“…For decades, the building of strong relationships in a business relationship environment has been founded on relationship marketing (RM) principles such as trust, commitment and satisfaction (Barroso-Méndez et al , 2014; Cyr, 2008; Kao and Lin, 2016; Mikkelson et al , 2016). In the 1990s, the seminal work of Morgan and Hunt (1994) highlighted the need for an RM approach towards relationship building that is based on the core principles of trust and commitment.…”
Section: Introductionmentioning
confidence: 99%